Effect of pH, temperature and agitation on thermophilic biohydrogen production using immobilized cells on carbon composites (GAC-NiFe3O4) - Mohd Jamaludin, Nina Farhana; Engliman, Nurul Sakinah; Abdul Manaf, Shareena Fairuz; Idrus, Syazwani; Abdullah, Luqman Chuah; Jamali, Nur Syakina (Elsevier, 2024)
Carbon composites-immobilized cell was utilized to enhance biohydrogen production. The initial pH, temperature and agitation effect was studied using the one-factor-at-a-time (OFAT) method. The optimal initial pH obtained was at pH 6.0 with hydrogen yield (HY) of 2.66 ± 0.09 mol H2/mol sugar, correlating with Gompertz constant of Hm = 974.99 mL, Rm = 17.90 mL/h and λ = 1.70 h. At 60 °C, the highest HY was obtained at 2.75 ± 0.11 mol H2/mol sugar. These corresponded to the Gompertz constant of Hm = 934.58 mL, Rm = 18.78 mL/h and λ = 1.89 h. The optimal agitation obtained was at 120 rpm, attaining the highest HY of 3.44 ± 0.54 mol H2/mol sugar, corresponding to the Gompertz constant of Hm = 1054.86 mL, Rm = 24.37 mL/h and λ = 3.90 h. The rRNA sequencing result revealed that the predominant species in the study was Thermoanaerobacterium. This study provides critical insight into process control conditions on biohydrogen production.